Comparison of Facial Soft Tissue Thickness in Males and Females and Class I Skeletal Pattern - Z Ghaffari (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Proportional relationship between different facial structures, including soft tissue thickness and dental and skeletal components, is the key to beauty. Today facial soft tissue harmony is the primary goal of orthodontic treatment, unlike the past which focused only on hard tissue and dental occlusion. The aim of this study was to measure facial soft tissue thickness in the northern population of Iran with class I skeletal pattern in lateral cephalometry and compare these values between males and females to use the results in orthodontic treatment and craniofacial reconstructions. METHODS: In this cross-sectional research, 180 lateral cephalometry of 77 male and 103 female, aged between 18-24 years who had referred to private orthodontic offices, were traced on acetate paper. Then, 10 anatomical variables were measured in Glabella, Nasion, Rhinion, Subnasal, Upper lip, Stomion, Lower lip, Labiomental region, Pogonion and Menton parallel to the Frankfurt plan. FINDINGS: Facial soft tissue thickness in males was significantly higher than females in Nasion (male=5.65±1.55, female=4.38±1.47), Rhinion (male=3.07±0.64, female=2.5±0.57), Subnasal (male=16.39±2.55, female=14.05±1.44), Upper lip (male=15.51±2.29, female=13.57±1.64), Lower lip (male=16.48±1.85, female=14.64±1.39), Labiomental (male=11.02±1.46, female=10.49±1.67) and Pogonion (male=11.4±1.64, female=10.32±1.77) (p<0.05). CONCLUSION: Based on the results of this study, there was a significant difference in facial soft tissue thickness between the two genders in the north Iranian population so that males had more facial soft tissue thickness than females in most of the areas.